Planificación Financiera De La Empresa Colbapi S.A., Provincia De Los Ríos - Colombatti Bueno, Erick Eduardo (2018)
Financial planning is performance that allows you to measure the degree to which managers perform their duties and execute their work properly, it is one of the tools most used by most organizations because they are generated through this procedures, methods and information with which managers can take the best decisions in order to achieve the achievement of financial objectives and goals that are expected get to the future. The company is in a highly competitive market, as there is a large number of companies dedicated to this end, without considering that in this market also The importers and representatives of the different brands are directly involved in what even more difficult the sale of products. In this type of business, different types of business are used strategies in order to please customers especially in quality, variety and service. The importance of carrying out this topic lies in knowing if there is planning in the company, that is to say a system through which it manages to elaborate and execute a financial plan technically raised. The main objective of this research is to determine the incidence of planning in the management carried out by the company for the maximization of profits, the minimization of financial risks and the correct administration of their resources, identifying the strengths, opportunities, weaknesses and threats that the company, in addition to the effect caused by the lack of financial planning. To theoretically support the research carried out, the quality of the study was reinforced having definitions and concepts of financial planning methods; for the purpose of Check whether in the hardware store COLBAPI S.A. comply with the respective processes of said planning: as well as evaluating the organization in its sales forecasts, various data operations in their economic and financial activities that provide specific information and timely of the projected situation for future periods, the method was very useful descriptive that allowed to carry out each of the procedures and thus meet the planted objectives.